Standardisation in Documentation and Book Science - Gopinath, M. A. (Journal of Information and Knowledge, 1972)
Standardisation and documentation emerged as organised activities during the first half of the twentieth century. Conservation of resource and increasing productivity in every sphere of activity was the goal. Standardisation can be provided for in two Forms : One in the form of a specification and the other in the form of guiding principles. Certain areas in the field of documentation and book science are amenable for standardisation in either one or both ways. The organisation and objectives of the Documentation Committees of the Indian Standards Institution, the British Standards Ins itution, the USA Standards Institute, and the International Standards Organization are described. The areas in documentation and in book science that are amenable for specification and/or guiding principles are mentioned. Published standards are also mentioned.